2015
DOI: 10.5649/jjphcs.41.275
|View full text |Cite
|
Sign up to set email alerts
|

Communication Form of Cooperation between Hospitals and Health Insurance Pharmacies Designed Based on the Results of a Questionnaire Survey on Cancer Patients and Community Pharmacists

Abstract: The rate of extramural prescription in Nagoya Memorial Hospital is approximately 90% and most of our patients receive medicine in health insurance pharmacies. However, there are several problems in the prescriptions for outpatients; the patients are sometimes unable to obtain the prescribed drugs because they are out of stock in the family pharmacy. In addition, community pharmacists find it difficult to instruct individual patients when obtaining information only through externally dispensed prescriptions. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Benefits of economic and prescription optimization from PBPM in accordance with community pharmacy and hospital pharmacy have also been reported [8]. Though similar efforts have been reported for chemotherapy, there are no reports that indicate their clinical benefits clearly [9][10][11][12]. A past research study reported that more than half of community pharmacists rarely feedback patient information to hospitals, and 14.3% community pharmacists rarely performed tasks such as continuous side effect monitoring and patient guidance, including supportive care [13].…”
Section: Discussionmentioning
confidence: 88%
“…Benefits of economic and prescription optimization from PBPM in accordance with community pharmacy and hospital pharmacy have also been reported [8]. Though similar efforts have been reported for chemotherapy, there are no reports that indicate their clinical benefits clearly [9][10][11][12]. A past research study reported that more than half of community pharmacists rarely feedback patient information to hospitals, and 14.3% community pharmacists rarely performed tasks such as continuous side effect monitoring and patient guidance, including supportive care [13].…”
Section: Discussionmentioning
confidence: 88%
“…Currently, one-half of Japanese people have cancer, and cancer treatments are increasingly being provided in outpatient settings [19]. However, due to the lack of the stock of medications, some cancer patients with externally prescribed medications cannot receive these medications at health insurance pharmacies [17]. In addition, community pharmacists often have trouble communicating with cancer patients, mainly because they lack patients' information, including the exact diagnosis, stage of malignant disease, treatment policy, and the status of informed consent from the patients in general [20].…”
Section: Discussionmentioning
confidence: 99%
“…We collaborated with the regional dental associations [21,22]and the facilities of palliative care and home care [23]using the information sheet to increase the quality of life in cancer patients. This multi-professional collaboration consequently led to repeated discussions with the regional pharmaceutical associations near our hospital (Tenpaku-ku, Midori-ku, and Nisshin-shi), during which we decided to create a communication sheet for pharmaceutical cooperation [17]. Based on the results of the questionnaire survey conducted after the use of the communication sheet, the original communication sheet was modified, and a unified reply form was added.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations